Correlation of three variables describing nasal patency (HD, MCA, NOSE score) in healthy subjects - Braun, Thomas; Rich, Maria; Kramer, Matthias F. (Brazilian journal of otorhinolaryngology, 2013)
Rhinoresistometry and acoustic rhinometry are two established apparative methods to objectify the respiratory function of the nose. Both methods use different variables to describe nasal patency: “hydraulic diameter”, HD, in rhinoresistometry, and “minimal cross-sectional area”, MCA1 (nasal isthmus) and MCA2 (head of the inferior turbinate and cavernous body of the nasal septum), in acoustic rhinometry. This study analyzes the mutual correlation of HD and MCA as a pilot study in patients without nasal pathologies. Additionally, we investigated if these objective variables correlate with the NOSE score, a validated tool to measure subjective perception of nasal patency. Planned data collection in a collective of 24 healthy subjects without nasal pathologies. Statistically significant, weak to moderate correlations were found between HD and MCA2 before decongestion. A moderate correlation was found between both HD and MCA2 and the NOSE score on the narrower side. In the assessment of nasal patency, it seems advisable to determine HD, MCA1 and MCA2, but also a subjective variable such as the NOSE score, which all seem to be not fully redundant variables. In further studies, the correlation of the variables should be assessed in patients with nasal pathologies.